Precise anatomical resection based on structures of nerve and fibrous tissue around the superior mesenteric artery for mesopancreas dissection in pancreaticoduodenectomy for pancreatic cancer. (11th March 2020) - Nagakawa, Yuichi; Yi, Shuang‐Qin; Takishita, Chie; Sahara, Yatsuka; Osakabe, Hiroaki; Kiya, Yoshitaka; Yamaguchi, Hiroshi; Miwa, Yoko; Sato, Iwao; Tsuchida, Akihiko
Abstract: Background: The aim of the present study was to investigate the feasibility of resection based on the nerve and fibrous tissue (NFT) structures around the superior mesenteric artery (SMA) for resectable pancreatic adenocarcinoma (R‐PDAC) patients. Methods: NFTs around the SMA were classified into four " intensive NTFs area" with spreading the NFTs around the SMA and three SMA nerve plexus regions without branching nerves according to autopsy findings. Complete dissection of four " intensive NTFs areas" was performed by pre‐exposing three SMA nerve plexus regions without branching nerves as " dissection‐guiding points" with SMA nerve plexus preservation (NFT‐based resection). Among 157 R‐PDAC patients undergoing pancreaticoduodenectomy, surgical outcomes of 78 patients with NFT‐based resection were compared with 59 patients with half‐SMA nerve plexus dissection and 20 patients without NFTs dissection. Results: In the NFT‐based resection group, 76.5% had tumor involvement and metastasis in each intensive NTFs area . Operative time, blood loss, and postoperative diarrhea rate were significantly lower in NFT‐based resection than in half‐SMA nerve plexus group (321 vs 390 min; P < .01, 228 vs 550 mL; P < .01, 5.1% vs 15.3%; P = .04, respectively). R0 rate and median overall survival significantly improved in NFT‐based resection than in non‐NFT dissection group (93.6% vs 65.0%; P < .01, 49.6 vs 23.6 months, P = .01). Conclusion: NFT‐based resection may become a novel method for R‐PDAC patients. Abstract : Highlight In pancreaticoduodenectomy for resectable pancreatic cancer, there are no uniform criteria for determining the appropriate dissection area around the superior mesenteric artery during surgery. Nagakawa and colleagues describe a novel concept for precise anatomical resection on the basis of the nerve and fibrous tissue structures around the superior mesenteric artery.